Influence of audience on the home advantage: a comparative study in French Rugby union and Football championships before and during Covid-19 pandemic - Thon, B.; Doutreloux, J.-P. (Movement & Sport Sciences - Science & Motricité, 2024)
Several sources suggest that the behavior of supporters is as important as their number in the stadium in influencing the advantage of playing at home in team sports. Some studies indicate that Football fans display more violent behaviors than Rugby ones and we hypothesized that they contribute more importantly to the home advantage. We analyzed the performances of the teams involved in the highest level of Rugby union and Football French championships during 2019-2020 season (with fans in the stadiums) and the 2020-2021 season (without public). Results revealed that the advantage of playing at home is significant when public was present in both sports. However, when fans were not present, this advantage disappeared in Football but remained unchanged in Rugby union. So, crowd attendance is an important factor in determining Home advantage (or Away disadvantage) in Football, but not in Rugby union. These results are discussed in terms of differences in fans behavior in the two sports, and we hypothesized that the feeling of territoriality is more important in Rugby union than in Football.